Pemberdayaan Perempuan Melalui Implementasi Strategi Program Peningkatan Kualitas Hidup Dan Perlindungan Perempuan Di Provinsi Riau - Puja Afwanda Mayako; Zaili Rusli; Adianto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
The program to improve the quality of life and protection of women in Riau Province is a program that functions to empower women victims of domestic violence. This study aims to determine the strategy implementation of life quality improvement and protection of women program in Riau Province, as well as determining the inhibiting factors of the program. This study uses qualitative research with a descriptive case study approach. The research results found that the implementation of the strategy program improved quality of life and protection of women in Riau Province is good. Because of all the assessments done on the program, budgets and procedures, all of them show the results that are already good. Implementation of the strategy of the program conducted by the Women Empowerment Office and Child protection of Riau Province through UPT P2TP2A which is reviewed from the program has been running for more than a year and the benefits of this program has been perceived by victims of domestic violence that received treatment. A review from the budget indicates that the budget used has been audited and recorded in the document of the budget work plan so that it can be accounted for. Then reviewed from the procedure shows that in the implementation of quality of life improvement program and women protection is executed according to the operational standards of the existing procedures.